Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1037/a0035773
|View full text |Cite
|
Sign up to set email alerts
|

Treating the untreatable: A single case study of a psychopathic inpatient treated with Schema Therapy.

Abstract: From its first conceptualization in modern psychiatry, psychopathy has been considered difficult if not impossible to treat. Schema Therapy (ST) is a psychotherapeutic approach that has shown efficacy in patients with borderline personality disorder. ST has recently been adapted for personality disordered forensic patients, including patients with high levels of psychopathy. The present case study examined the process of individual ST, combined with movement therapy and milieu therapy by the nursing staff, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 64 publications
2
31
0
1
Order By: Relevance
“…Chakhssi, Kersten, de Ruiter, and Bernstein () described Andy, a young man who had been incarcerated for a sexually violent offense who had a high score on a measure of psychopathy. While recounting to his clinician how he could not trust other inmates, Andy became increasingly aroused and controlling.…”
Section: Personality Disorder Dynamicsmentioning
confidence: 99%
“…Chakhssi, Kersten, de Ruiter, and Bernstein () described Andy, a young man who had been incarcerated for a sexually violent offense who had a high score on a measure of psychopathy. While recounting to his clinician how he could not trust other inmates, Andy became increasingly aroused and controlling.…”
Section: Personality Disorder Dynamicsmentioning
confidence: 99%
“…In this way of studying the possible relationship between these two disorders, the study by Chakhssi, et al [29] focused on a clinical case in which a schema therapy treatment is applied to a forensic patient with psychopathic features. Schema therapy is a psychotherapeutic approach with demonstrated efficacy in patients with borderline personality disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, both studies have studied the efficacy of treatments applied to BPD, such as scheme therapy [29] or Dialectical Behavior Therapy (DBT) [28], in psychopathic patients, obtaining in both cases positive results.…”
Section: Conflicts Of Interest and Source Of Fundingmentioning
confidence: 99%
“…This was then formally tested in a three-year randomized trial (N = 86) comparing schema therapy to transference-focused therapy. Chakhssi, Kersten, de Ruiter, and Bernstein (2014) have recently outlined a detailed case study of this approach for a forensic patient with personality disorder over a four year treatment period. A follow up implementation study demonstrated similar effect sizes when used in routine clinical practice and without the out of hours phone support which was a component of the treatment approach of the first trial (Nadort et al, 2009).…”
Section: Stage Two: Randomized Clinical Trials and Schema Mode Model mentioning
confidence: 99%